Feeding and reproduction of the blue shark, Prionace glauca (Linnaeus, 1758), off Southeastern and Southern Brazil - Bornatowski, Hugo; Schwingel, Paulo Ricardo (Arquivos de Ciências do Mar, 2008)
Sampling of individuals of Prionace glauca was carried out using a surface long-line in four research cruises of the R.V. Soloncy Moura, of the IBAMA/CEPSUL Institute, in December, 2002, and March, April and July, 2003. A total of 61 individuals were captured (31 females and 30 males) in 20 hauls of the fishing gear. Gut contents from only 11 individuals could be analyzed, whereby the feeding diet was seen to be based on small Teleostei and Cephalopods, mainly the fishes Aluterus sp., Balistes sp. and Diodon sp., and the squids Illex argentinus and Chiroteuthis veranyi . The estimate of uterine fecundity of P. glauca , which presents a viviparous development, was 34.2 embryos/eggs per female. There was found to occur a synchronism in the embryonic development to the effect that in December and April (summer and autumn), when embryos reach were 3 to 12 cm TL long, and females were beginning their pregnancy; and in July, when embryos were 24 cm TL long, and the females would be in about their fourth month of pregnancy. This synchronism may vary due to the occurrence of females with eggs implanted on the womb from December till next year’s July. The results obtained in this work suggest that P. glauca use the studied area for pregnancy and birth.